Pharmacodynamic Properties Of Extracts From Different Parts Of Euphorbia Hirta On Staphylococcus Epidermidis And Shigella Sonnei. - Jalil Kader,; Nur Aishah Abdul Wahab; Hanina Mohd Noor; Salina Mat Radzi (Asian Journal of Biochemical and Pharmaceutical Research, 2024)
The different parts of Euphorbia hirta which are whole plants, flowers, stems, leaves and roots showed high antibacterial activity against two strains of bacteria namely Staphylococcus epidermidis and Shigella sonnei. In this present study, attempt was made to evaluate the pharmacodynamic properties of the different parts of E. hirta on those strains. The treatment of E. hirta extracts towards S. epidermidis and S. sonnei indicated the bactericidal activity in the kinetic study and significant PAE values on the treatment. Among E. hirta parts tested, whole plant extracts indicated fast killing effects via time-kill kinetics (kinetic study) for both strains. All the different parts of E. hirta extracts exhibited the significant PAE values (0.5 h and above) against strains tested. The kinetic study and PAE data basically indicated the stronger effect of E. hirta extracts toward S. epidermidis compared to S. sonnei.